2021
DOI: 10.1167/iovs.62.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences and Physiologic Behaviors in Peripapillary Scleral Fibroblasts

Abstract: The purpose of this study was to describe the cellular architecture of normal human peripapillary sclera (PPS) and evaluate surface topography's role in fibroblast behavior. METHODS.PPS cryosections from nonglaucomatous eyes were labelled for nuclei, fibrillar actin (FA), and alpha smooth muscle actin (αSMA) and imaged. Collagen fibrils were imaged using second harmonic generation. Nuclear density and aspect ratio of the internal PPS (iPPS), outer PPS (oPPS), and peripheral sclera were determined. FA and αSMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Fibroblasts cultured on a surface with grooved topography align with the long axis of the grooves. We previously demonstrated that the combination of TGFβ treatment and cyclic uniaxial strain applied parallel to the direction of these grooves reduced fibroblast cell body alignment with surrounding topography 7 . Here, we expand on those findings by examining fibroblast-ECM alignment at baseline, following 18 hours of cyclic strain (1 Hz, 5% strain), and after a 24-hour recovery period during which the strain was stopped.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroblasts cultured on a surface with grooved topography align with the long axis of the grooves. We previously demonstrated that the combination of TGFβ treatment and cyclic uniaxial strain applied parallel to the direction of these grooves reduced fibroblast cell body alignment with surrounding topography 7 . Here, we expand on those findings by examining fibroblast-ECM alignment at baseline, following 18 hours of cyclic strain (1 Hz, 5% strain), and after a 24-hour recovery period during which the strain was stopped.…”
Section: Resultsmentioning
confidence: 99%
“…The sclera is relatively paucicellular but contains populations of macrophages, stem cells, and fibroblasts [4][5][6] . Resident fibroblasts are the main scleral cellular component and can be found throughout the sclera with high cytoskeletal alignment to surrounding extracellular matrix (ECM) 7 . Oglesby and colleagues showed fibroblast proliferation after IOP elevation and increased aSMA expression which is a marker for myofibroblasts -a cell type involved in tissue remodeling throughout the body 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this pattern correlates with distribution and alignment of scleral fibroblasts. Fibroblast density increases in proximity to the ONH, and fibroblast projections are highly aligned with collagenous structures [ 112 ]. There is also limited evidence to suggest that such fibroblast density gradients may exist in mouse as well [ 113 ].…”
Section: Scleral Fibroblastsmentioning
confidence: 99%
“…Given this precise alignment of fibroblasts and collagen, these cells likely play a role in the detection of tissue stretch. The reaction of fibroblasts may also differ based on localization as α-SMA expression appears to disrupt fibroblast projection alignment with collagen in the peripheral sclera, but not the ppScl, and fibroblast orientation is most altered when cells detect both strain and TGF-β signaling simultaneously [ 112 ]. These synergistic processes likely reinforce chronic glaucomatous remodeling of the ppScl, altering its biomechanical properties.…”
Section: Scleral Fibroblastsmentioning
confidence: 99%